Organisational climate: Conceptualisation and measurement in an ODL HEI - Grobler, Sonja; Grobler, Anton (South African Journal of Higher Education, 2016)
Higher education institutions (HEIs) need to improve their work environment to ensure an environment conducive to learning, including a healthy organisational climate, as one of the important aspects of sustainability. The first objective of the current study was to conceptualise organisational climate within an HEI and specifically one in an open distance learning (ODL) environment. The conceptualisation was done through the construction of an organisational climate questionnaire standardised for the ODL HEI. Secondly, the objective was to determine the psychometric properties of the newly constructed organisational climate questionnaire. A survey design was followed with a questionnaire, consisting of an item pool of 90 questions, which was administered to 2 086 personnel members of an ODL HEI. Six factors, with acceptable psychometric properties, were extracted using a factor analysis method. These factors were labelled leadership, my manager, organisational citizenship, compensation, interpersonal relationships and clients, capacity and values.